Research-Based Pocket Book as Fungi Learning Media - Lilis Supratman; Yamin Yamin (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
Fungi endophytic is microscopic so that the results of the documentation of the research can be documented in the form of a pocket. The book pocket is a media of learning that are practical and easy to carry anywhere. In this pocket-book, outlined that the fungi endophytic obtained on the organs of Ciplukan plants namely roots, stems and leaves. Fungi endophytic obtained four isolate suspected of having a substance compound antimicrobials against pathogenic bacteria. Test the feasibility of a pocket book to be used as a source of learning has been validated by experts learning media and material experts. Validation results show an average of 84.31% resulting in valid criteria. The validators statement based on validation states pocketbooks can be used as a source of learning.